Attitude of Postgraduate Medical and Nursing Students towards Inter-professional Learning - Nazi Noor, Samina Kousar, Rozina Malik, Rizwana Yasmin, Shazia Emennual, Afshan Mehwish Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Globalisation, newly discovered diseases, and technological improvements have been noted to have significantly altered the healthcare system in recent years, which is continuously affecting healthcare outcomes. These adjustments necessitate standard care from medical specialists, who must be highly motivated to collaborate as a team. Aim: To assess and compare the attitudes of postgraduate medical and nursing students towards inter-professional learning. Study design: Comparative cross-sectional study. Methodology: Purposive sampling approach and a comparative cross-sectional study design were used to study postgraduate medical and nursing students from the University of Health Sciences and the University of Lahore. One hundred twenty (120) of the three hundred and twelve (312) postgraduate medical and nursing students who were contacted for data collection completed the survey. The 19 items of the RIPL, or Readiness to Inter-professional Learning Scale, were used to collect the data. In order to analyze the data, SPSS 23 was used. Results: Ages of study participants ranged from 21 to 52, with a mean of 32.4 +/- 6.4. 62 (51.7%) and 58(48.3%) of the 120 people were from the University of Health Sciences, Lahore, respectively. The mean readiness score on the Inter-professional Learning Scale, with a range of 42 to 86, was 72.4 6.97 overall. In the categories of duty and responsibility and teamwork and collaboration, there was no appreciable difference between postgraduate medical and nursing students' mean attitudes scores. Practical Implication: IPL as a pedagogical tool because it gives the concepts of collaborative practice, as represented by the IPL idea, a framework. Students must always be prepared to participate in inter-professional learning if IPL is to be successfully promoted, as doing so will expand their knowledge, skills, and understanding of responsibilities of healthcare professionals. Conclusion: It was concluded that early adoption of inter-professional learning programmes at the beginning of professional training and the provision of a suitable learning environment for healthcare learners will promote collaboration and cooperation in clinical settings, which may also improve patient and family satisfaction. Keywords: Inter-professional Learning, Post-graduate Nurses, Knowledge and Attitude.